2017
DOI: 10.1128/jvi.01051-17
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Correlates of Simian Immunodeficiency Virus-Associated B Cell Dysfunction

Abstract: We compared and contrasted pathogenic (in pig-tailed macaques [PTMs]) and nonpathogenic (in African green monkeys [AGMs]) SIVsab infections to assess the significance of the B cell dysfunction observed in simian (SIV) and human immunodeficiency virus (HIV) infections. We report that the loss of B cells is specifically associated with the pathogenic SIV infection, while in the natural hosts, in which SIV is nonpathogenic, B cells rapidly increase in both lymph nodes (LNs) and intestine. SIV-associated B cell dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 110 publications
(141 reference statements)
1
16
0
Order By: Relevance
“…As pathogenic SIV infections are associated with B-cell dysfunction [76], we next assessed the fate of CD20 + B-cell populations during the earliest stages of SIVsab infection of AGMs,…”
Section: Plos Pathogensmentioning
confidence: 99%
“…As pathogenic SIV infections are associated with B-cell dysfunction [76], we next assessed the fate of CD20 + B-cell populations during the earliest stages of SIVsab infection of AGMs,…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Furthermore, vaccine-elicited antibody responses in the RV144 efficacy trial were mapped to both conformational and linear V2 epitopes, suggesting that V2-specific IgG responses with anti-viral activity may not only target linear V2 epitopes [ 9 , 14 ]. Interestingly, it has been shown that conformational epitope recognition of SIV Env-specific antibody responses differs greatly between nonpathogenic and pathogenic SIV infections in natural SIV hosts [ 23 ]. Thus, ADCC-mediating IgG responses in humans and AGMs may target both linear V2 and conformational gp120 epitopes within HIV and SIV Env.…”
Section: Discussionmentioning
confidence: 99%
“…SIV Env-specific IgG responses in chronically SIV-infected AGMs more frequently target gp120 epitopes compared to SIV-infected RMs [ 20 ]. While previous studies reported that B cell depletion in SIV-infected AGMs has no appreciable effect in disease progression outcome [ 22 ], it has also been shown that SIV-associated B cell dysfunction is associated with pathogenic SIV infection, and not in non-pathogenic SIV infection in natural SIV hosts [ 19 , 23 ]. Moreover, we previously demonstrated that SIV Env gp120-specific IgG monoclonal antibodies (mAbs) isolated from chronically SIV-infected AGMs mediated robust virus capture activity, and ADCC—an antibody function that has been associated with delayed progression to AIDS in RMs [ 20 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whole blood was stained to monitor the impact of RMD on the immune cell populations. TruCount was used to determine absolute counts of CD3 + , CD4 + , CD8 + T cells and CD20 + B cells as described (51)(52)(53). Fifty microliters of whole blood were stained with antibodies against CD3-V450, CD4-APC, CD20-APC-H7, and CD45-PerCP in TruCount tubes (BD Biosciences, Franklin Lakes, NJ, USA) with a set number of fluorescent beads as internal standards.…”
Section: Flow Cytometrymentioning
confidence: 99%